2017
DOI: 10.1038/s41598-017-02602-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection in Commercial Perennial Crops: Applicability and Improvement in Oil Palm (Elaeis guineensis Jacq.)

Abstract: Genomic selection (GS) uses genome-wide markers to select individuals with the desired overall combination of breeding traits. A total of 1,218 individuals from a commercial population of Ulu Remis x AVROS (UR x AVROS) were genotyped using the OP200K array. The traits of interest included: shell-to-fruit ratio (S/F, %), mesocarp-to-fruit ratio (M/F, %), kernel-to-fruit ratio (K/F, %), fruit per bunch (F/B, %), oil per bunch (O/B, %) and oil per palm (O/P, kg/palm/year). Genomic heritabilities of these traits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
1
30
0
3
Order By: Relevance
“…In addition, the difficulty and costs associated with these long term evaluations limit the number of individuals evaluated, resulting in low selection intensity. In this context, the potential of GS for palm oil yield is high, and has been confirmed in the few previous studies dealing with GS in this species [ 15 19 ].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, the difficulty and costs associated with these long term evaluations limit the number of individuals evaluated, resulting in low selection intensity. In this context, the potential of GS for palm oil yield is high, and has been confirmed in the few previous studies dealing with GS in this species [ 15 19 ].…”
Section: Introductionsupporting
confidence: 71%
“…Nevertheless, the empirical GS studies published in oil palm so far [ 17 19 ] suffered from some limitations. First, like in many studies in other crops, they used single datasets which can bias accuracies upwards [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Costs for GS ranged from US$75,000 to $194,000 per unit gain, depending on cost per marker data point, population size, QTL number and heritability, compared with US$116,000 to $333,000 per unit gain for 19 years of phenotypic selection per cycle. Also in oil palm, Kwong et al (2017a) found that for 1,218 individuals genotyped using a 200K array, GS model accuracy increased with trait heritability, ranging from 0.40 to 0.70.…”
Section: Yield Prediction Using Genomic Selectionmentioning
confidence: 99%
“…Denis and Bouvet (2013) concluded that perennial crops may have more to gain from GS than annual crops since genetic gain per unit time in perennial crops is critical for improved cultivars. There is a paucity of published studies for tree nut crops, though there has been some work conducted in citrus (Minamikawa et al 2017), apple (Kumar et al 2012b), oil palm (Wong and Bernardo 2008;Kwong et al 2017a), and pear (Iwata et al 2013;Minamikawa et al 2018). In a recent study of fruit quality traits in Japanese pear, model accuracy was highest when data for parents and progeny were combined, at r > 0.7 for most traits (Minamikawa et al 2018).…”
Section: Yield Prediction Using Genomic Selectionmentioning
confidence: 99%
See 1 more Smart Citation